Application of the Lawah Method for Learning Maharoh Kitabah in Madrasah Ibtidaiyah - Hidayah, Lutfi; Hafidah, Hafidah (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to find out the procedures for applying the lauh method in learning the Maharoh Kitabah in Arabic as well as its advantages and disadvantages in the learning process. This type of research is bibliography, the data collected in this study is in the form of secondary data. Data obtained from library research. The data collection technique used is literature study. The data analysis technique in this research uses qualitative analysis using deductive and inductive methods. The research results showed that the lauh method is a method of memorizing the Koran using a board. The procedure for learning maharoh kitabah is to choose 5-10 vocabulary words, then read them several times, and after that, write them down while reading the written vocabulary words. If they feel they have memorized the new student, they will submit their memorization to the teacher. This applies to all Arabic vocabulary. The advantages of this method are that it will be more thorough, the student's concentration will be more focused on the writing, and they will have trained patience. The disadvantages are that some students feel uneasy because they do not have writing skills. Students are reluctant to prepare and clean the blackboard before studying, because they are afraid of getting their hands dirty. Modern tools are starting to be used in the classroom learning process. There are many books that can be purchased. rather than using a board, and requires a lot of time when using a board.